Living in a dangerous neighbourhood : Iran and its quest for security through nuclear deterrence : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Politics at Massey University, Albany, New Zealand - Gharekhanian, Hamid (Massey University, 2015)
The ongoing dispute between Iran and certain members of the international community over Iran’s nuclear programme has attracted academic debate, significant media attention, and much diplomatic anxiety over the past two decades. While the Iranian Government maintains that its nuclear programme is based upon peaceful purposes and primarily aimed at enhancing energy efficiency to meet the country’s increasing domestic demand, this thesis argues that key factors informing Iran’s nuclear ambitions include its overarching security concerns which transcend the use of nuclear energy for economic ends. Iran’s nuclear policy has largely been shaped by the insecurities caused by its neighbouring countries, some of which are nuclear-armed states. Iran’s sense of insecurity has been compounded by the presence of US armed forces in the region, whose military superiority cannot be overcome by Iran’s conventional army alone. This thesis contends that Iran’s leaders continue to pursue a nuclear programme in the face of the international community’s objections because they believe that nuclear weapons represent a credible military deterrent and, as such, form a vital part of its quest for national security.
Keywords: Nuclear weapons; Nuclear arms control; Military policy; Foreign relations; Iran; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science